What is the relationship between agricultural credit, cattle, and deforestation? A spatial analysis in Colombia - Mejía, Daniela; Díaz, Manuel Francisco; Enciso, Karen; Burkart, Stefan (International Center for Tropical Agriculture, 2021)
In developing countries, agricultural credit plays a vital role in supporting agricultural production and productivity increases. Together with other political and economic elements, credit can be a useful tool to promote innovation, improve resource allocation, and, properly targeted, help diminish inequality gaps, thereby generating a cycle of economic prosperity. However, and although the scope and amounts of the credit have increased over the years, some shortcomings associated with expansion processes have also become evident, generating discussion about the efficiency of this mechanism for productivity increases and, consequently, livelihood improvements of the rural population.